REAKTUALISASI AWIK-AWIK DALAM MELESTARIKAN SOSIAL BUDAYA MASYARAKAT DESA LANDAH KECAMATAN PRAYA TIMUR KABUPATEN LOMBOK TENGAH - Mohammad Liwa Irrubai (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This article aims to explain the results of the re-actualization Awig awig Desa in preserving the social and cultural Desa Landah Kecamatan Praya Timur, Kabupaten Lombok Tengah is done by optimizing the village officials and all elements of society in guarding Awig awig Desa both in the planning process, manufacture, fixing up to supervision. The research method used is descriptive qualitative research subject community leaders, village government and villagers Desa Landah. Data were collected through observation, interviews and documentation. The conclusion drawn by the domain analysis. The results showed that Awik-awik Desa Landah as follows: 1) Do not damage trees turi, 2) Non-destructive beans, 3) Do not take water from the stream before getting a turn, and 4) not infringe customs. Reactualization Awig awig Desa in preserving the social and cultural village Landah conducted by Religious Leaders, Community Leaders, Indigenous Leaders, Youth Leaders, Women Leaders, Head of Hamlet or keliang, Chairman of RT, and philter. Furthermore Awig awig Desa disseminated to the general public through village meetings, village meetings, neighborhood meetings, religious events and announcements through panflet.